Effects of 1-Methylcyclopropene Treatment on Physicochemical Attributes of “Hai Jiang” Yardlong Bean during Cold Storage - Zitao Jiang; Jiaoke Zeng; Yunke Zheng; Hong Tang; Wen Li (Journal of Food Quality)
The yardlong bean belongs to nonclimacteric fruit. The objective of this study was to investigate the effects of 1-methylcyclopropene (1-MCP) treatment on physicochemical characteristics of yardlong beans during cold storage. Freshly harvested yardlong beans were treated with different concentrations of 1-MCP (0, 0.75, 1.0, 1.25, and 1.5 μL ·L−1) and stored at 8°C for 21 days. The results showed that, compared with the control, the decrease in firmness and good fruit rate and the degradation of chlorophyll and vitamin C (Vc) content could be inhibited, change in skin color could be delayed, activities of superoxide dismutase (SOD) and peroxidase (POD) could be improved, and the increasing of malondialdehyde (MDA) content and weight loss could be inhibited significantly by 1-MCP treatments. Of the different concentrations of 1-MCP, 1.0 μL·L−1 proved to have the best preservative effects, extending storage time and delaying ripening and senescence of yardlong beans. These results indicated that 1-MCP treatment provided an effective method for delaying the postharvest senescence of fresh yardlong beans.